AN ANALYSIS OF MODULATION TRANSLATION TECHNIQUE OF PHRASAL VERBS IN FIVE BBC NEWS ARTICLES - Fristi Arfiawati; Silvie Nabilah (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The research that entitled An Analysis of Modulation Translation Technique of Phrasal Verbs in Five BBC News Articles purposed to analyze the types of Translation Technique based on Newmark (1988) and Molina & Albir (2002) theory. The research applied descriptive qualitative method and used BBC News Articles as the data. The data were taken from five BBC News Articles and analyzed by using the theory of kinds of Translation Technique. The research focus on modulation technique translation of phrasal verbs in BBC News Article. Modulation technique of translation change the point of view, focus or cognitive, category in relation to the source text which it can be lexical or structural. The result showed that there were nine modulation techniques which is employed in the translation of phrasal verbs in five BBC News Article.